Minimizing normal vehicle forces effect during cornering of a two in-wheel vehicle through the identification of optimum speed via particle swarm optimization - Nurul Afiqah, Zainal; Kamil Zakwan, Mohd Azmi; Muhammad Aizzat, Zakaria; Abdul Majeed, Anwar P. P. (Springer, 2021)
Driving comfort is a non-trivial issue as it could pose adverse health issues particularly to those who travel-long distances. In the present study, we identify the optimum speed during cornering in order to reduce the effect of normal vertical forces towards driving experience of a two-in wheel vehicle. A bio-inspired metaheuristic method, namely Particle Swarm Optimization (PSO) was employed to address the objective of the present investigation on a twelve degrees of freedom human biodynamic model that is fused to a two-in-wheel car model. It was established through the PSO algorithm, that the optimal speed during cornering for the given car configuration is approximately 19 km/h. The findings of the present study are essential in ensuring human comfort is not compromised that in turn minimizes possible untoward risk to the driver.